Pengaruh Penambahan Abu Kulit Cacao terhadap Sifat Mekanik dan Morfologi Bata Merah - Masthura Masthura; Ratni Sirait; Rosyidah Mardiyah Sagala (Fakultas Teknik Universitas Cenderawasih, 2023)
The purpose of this research to effect variations cacao peel ash to parameters mechanical and morphology in making red brick. This research method uses the experiment. The research of characterization compressive strength value a minimum of 29,73 kg/cm2 and maximum of 243,82 kg/cm2. The morphology structure testing with software digimizer a minimum of 0,7985 μm, and maximum of 2,4551 μm. The composition of mixing clay, water, and cacao peel ash by increasing the burning temperature of bricks show the optimum test parameters at the temperature 1000℃ with variation in cacao peel ash is 20% that has the met the standard SNI 15-2094-2000.